THE EFFECT OF ORGANISATIONAL ACTIVITY AND SELF-EFFICACY ON STUDENT ACHIEVEMENT INDEX - Asri Nur Muin; Sukardi Sukardi; Muhammad Nurhusain (Jurnal Ekonomi, 2022)
This study aims to determine the effect of organisational activity and self-efficacy on student achievement indexes for students who are actively organised in the internal campus organisations of STIE YPUP Makassar and STKIP YPUP Makassar for the 2021–2022 period. Studying this is studying "ex post facto." Population study: This is the whole internal organisational management of the STIE YPUP Makassar campus and STKIP YPUP Makassar for the 2021–2022 period, with as many as 128 people who simultaneously become sample researchers. The results showed that organisational activity had a significant negative effect on the student achievement index, self-efficacy had a significant positive effect on the student achievement index, and both organisational activity and self-efficacy had a significant effect on the student achievement index. Based on these results, it was found that students who were active in organisations but did not have good self-efficacy had a negative impact on the achievement index obtained. Conversely, students who are active in organisations and have good self-efficacy will have good academic achievement scores; the higher their self-efficacy, the higher their learning achievement scored.